High Levels of Resistance to Metronidazole and Clarithromycin in Helicobacter pylori Strains in Children - Kalach, Nicolas (American Society for Microbiology, 2001)
The aim of the study was to evaluate the prevalence of resistance to amoxicillin, metronidazole, and clarithromycin before treatment of Helicobacter pylori infection in children and to assess the evolution of resistance with time. The study was carried out between 1994 and 1999 with 150 H. pylori-positive children through gastric culture (antimicrobial susceptibility) and histology. All cultured H. pylori strains were sensitive to amoxicillin, 64 (43%) were resistant to metronidazole, 32 (21%) were resistant to clarithromycin, and 14 (9%) were resistant to both metronidazole and clarithromycin. The overall prevalence of resistance to metronidazole and clarithromycin did not change significantly with time. The study highlights the generalized high-level and stable metronidazole and clarithromycin resistance of H. pylori strains from children.